Atypical bromethalin intoxication in a dog: pathologic features and identification of an isomeric breakdown product - Bates, Maria C. (BMC Vet Res, 2015)
BACKGROUND: Definitive post mortem confirmation of intoxication by the neurotoxic rodenticide bromethalin can be challenging. Brain lesions are not specific and detection of bromethalin and its metabolites are unpredictable due to rapid photodegradation and inconsistent behavior in tissues. CASE PRESENTATION: A 2-year-old dog presented with rapid onset of severe muscle tremors and death within hours after a known ingestion of a reportedly low dosage of bromethalin and subsequent decontamination using activated charcoal. Marked meningeal hemorrhages and multifocal myelin sheath vacuolation were observed in the brain. A marked reactive astrocytosis and neuronal hypoxia/necrosis were identified using immunohistochemistry (IHC) for glial fibrillary acidic protein (GFAP) and for neuron specific protein (NeuN). Bromethalin exposure and tissue absorption was confirmed by identification of one of two isomeric 543.7 molecular weight (MW) breakdown products in the patient’s adipose and kidney samples using gas chromatography (GC) combined with tandem quadrupole mass spectrometry (MS/MS). CONCLUSIONS: The severity of clinical signs and subsequent death of this dog was not expected with the low dosage of bromethalin reportedly ingested, and the use of activated charcoal possibly precipitated a hypernatremic status. Meningeal hemorrhages are atypical of bromethalin intoxication, and might have been caused by hyperthermia, secondary to tremors or hypernatremia. Identification of one of two isomeric breakdown products in the adipose tissue and kidney provides an additional molecule to the toxicologic testing regime for bromethalin intoxication.